Firewood as an Active Learning Methodology for Construction [la Leña Como Metodología de Aprendizaje Activo Para la Construcción] - Burgos-Leiva, C; Rodriguez-Garcia, A; Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2018)
This article shows the results of an intervention of the active type using electromagnetic technology. The motivating experience of the intervention manages to be the center of attention of the students in the classroom. In this way the teacher can establish a connection by developing the understanding of the concept of relative humidity in firewood. The intervention was carried out in the two semesters of 2017, in the construction materials class of the technology career in construction. The samples were of similar gender and age group. The measured variables were five, which determine the understanding of concepts such as: typification, classification, recognition and differentiation. The results obtained were significant, showing its enormous potential as an element to be used in the class. © 2018 Centro de Informacion Tecnologica.; El presente artículo muestra los resultados de una intervención del tipo activa utilizando tecnología electromagnética. La experiencia motivadora de la intervención logra ser centro de la atención de los estudiantes en la sala de clases. De esta forma el docente logra establecer una conexión desarrollando la comprensión de la humedad relativa en la leña. La intervención se realizó en dos semestres del año 2017, en la clase de materiales de construcción de la carrera Tecnología en Construcción. Las muestras fueron de similar género y grupo etario. Las variables medidas fueron cinco, las que determinan la comprensión de conceptos tales como tipificación, clasificación, reconocimiento y diferenciación. Los resultados obtenidos fueron significativos mostrando su enorme potencial como elemento de uso en la clase. © 2018 Centro de Informacion Tecnologica.